Peran Teknologi dalam Pengembangan Profesional Guru Madrasah Ibtidaiyah - Qamariyah, Nurul (Darul Yasin Al Sys, 2024)
In the context of increasingly digitized education, the role of technology in the professional development of Madrasah Ibtidaiyah teachers is an important area of concern. This study aims to explore the impact of technology on improving pedagogical skills, access to educational resources and collaboration among teachers, as well as the challenges faced in its implementation. The method used was a literature study, which included an analysis of current academic sources on the application of technology in education. The results show that technology, especially e-learning platforms and digital collaboration tools, can significantly improve pedagogical skills and student motivation, despite major challenges related to unmet infrastructure and training needs. The implications of these findings highlight the need for improved technology infrastructure, better training and institutional support to maximize the benefits of technology in education. This research provides a basis for the development of new models of technology integration that consider the local context and specific needs in Madrasah Ibtidaiyah education.